KHAMIR PENGHASIL LIPID YANG MEMANFAATKAN BIOMASSA LIGNOSELULOSA UNTUK PRODUKSI BIODIESEL - Ruli, Fitha Febrilia (Department of Biology, Faculty of Mathematics and Natural Sciences, Hasanuddin University, 2025)
Lignocellulosic biomass is an abundant and renewable carbon source with great potential for biodiesel production by oleaginous yeasts. These yeasts can accumulate high amounts of lipids when grown on lignocellulosic biomass, which primarily consists of glucose and xylose. However, the complex structure of lignocellulosic biomass requires pretreatment and hydrolysis steps to release fermentable sugars. This process often produces by-products in the form of inhibitors such as furfural, 5-hydroxymethylfurfural (HMF), and acetic acid, which can inhibit yeast growth. Therefore, oleaginous yeasts capable of simultaneously assimilating glucose and xylose and are tolerant to inhibitors, are needed to optimally utilize this substrate. This review discusses yeast species that can utilize lignocellulosic hydrolysates for growth, the types and compositions of available sugars, the mechanisms of sugar assimilation, and the impacts of inhibitors on lipid production. This review aims to provide a comprehensive understanding of the potential and challenges of using lignocellulosic biomass for biodiesel production by oleaginous yeast. Keywords: Lignocellulosic biomass, oleaginous yeast, lipid, inhibitor, biodiesel